Биоморфологическая характеристика Chlorophytum comosum (Thung) Baker при интродукции в Донецкий ботанический сад НАН Украины - Прилуцкая, С.А. (Промышленная ботаника, 2003)
Biomorphologic peculiarities of root system and shoot body in subtropic Chlorophytum comosum (Thung) Baker (Asphodelaceae A.L. de Jussieu family) species under introduction into the Donetsk Botanical Gardens, Nat. Acad. Sci. of Ukraine conservatories have been studied. The life form and phenorhythmotype have been determined. Schemes of structure (formation) and branching of the shoot body and inflorescence are suggested. A morphologic description of vegetative and generative organs is being made.